Meta review of systematic and meta analytic reviews on movement differences, effect of movement based interventions, and the underlying neural mechanisms in autism spectrum disorder - Miyahara, Motohide (Frontiers in Integrative Neuroscience, 2013)
Purposes: The aims of this paper are three-folds: first, to identify and appraise evidence from published systematic and meta-analytic reviews on 1) movement characteristics of individuals with autism spectrum disorders (ASD); 2) the effects of movement based interventions for ASD; 3) hypothesized underlying neural mechanisms for the movement characteristics. Methods: A meta review of published systematic and meta-analytic reviews on movement characteristics, structural and functional brain anomalies in ASD and the effects of movement based interventions for individuals with ASD between 1806 and October 2012. The methodological quality of the identified systematic and meta-analytic reviews was independently assessed by two assessors with the assessment of multiple systematic reviews (AMSTAR). Results: The search yielded a total of twelve reviews on the movement differences or the movement based interventions. The methodological quality of the reviews varied, but the review conclusions were similar. Although individuals with ASD generally perform less well than age-matched controls in developmental movement tasks, there are few exceptions whose movement abilities are intact. Most movement based interventions report their efficacies. However, all existing studies employ the research design that is inherently incapable of providing strong evidence, and they often fail to report the extent of psychosocial interactions within the movement interventions. The hypothesized neural mechanisms are still under development and speculative in nature. Conclusions: It is premature to designate movement disturbance as a core symptom of ASD. The effects of movement based interventions on ASD core symptoms need to be further validated by stronger evidence based on verified theoretical mechanisms linking ASD with movement disorders.